Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Audio Visual Terhadap Hasil Belajar Kognitif Siswa Pada Pembelajaran IPA Kelas IV SDN Gugus 12 Kota Bengkulu - Rahma Ginantia; Endang Widi Winarni; Abdul Muktadir (JURIDIKDAS, 2023)
This study aims to determine the effect of Problem Based Learning model assisted by audio-visual media on students' cognitive learning outcomes in science subjects of grade IV Elementary School in Cluster 12 Bengkulu City. This type of research is quantitative research. The research method used is quasi-experimental design. With the design type "the matching only pretest-posttest control group design". The population in this study was Elementary School of Cluster 12 Bengkulu City. The sampling technique used cluster random sampling technique. The samples in this study were class IV SDN 81 Bengkulu City as the experimental class and class IV SDN 99 Bengkulu City as the control class. The research instruments used were pretest and posttest of science cognitive learning outcomes given to experimental and control groups. The data analysis method in this study is quantitative analysis using descriptive statistics and inferential statistics, namely the t-test. From the results of the t-test calculation of the posttest value of students' science cognitive learning outcomes, namely tcount = 8.87 is greater than the ttable value = 1.67. It shows that there is a significant difference between the posttest scores of the experimental and control classes. Based on the results of the difference in the posttest scores of students' cognitive learning outcomes, there is a significant effect with a scale of 5% on the use of the Problem Based Learning model assisted by audio-visual media on students' cognitive learning outcomes in science subjects of grade IV Elementary School in Cluster 12 Bengkulu City.